Hospitality in the Notational Plane - Ranganathan, S. R.; Bhattacharyya, Ganesh (Journal of Information and Knowledge, 1966)
After showing the prepotence of the work in the Idea Plane, illustrates how the poor capacity of the Notational Plane had been inhibiting the former. Traces the gradual development of the increase of Hospitality of the Notational Plane from the Pure Notational Base of 10 digits of DC to the Mixed Notational Base of 60 digits and the capacity of an array to as high as 901 Array Isolate Numbers in CC. Describes how the cohcepts of Empty Digits, Zones, and Sectors have increased the capacity of an Array in CC. Describes the use of the newly postulated Emptying Digits in, making potentially infinite both extrapolation in an array and interpolation at any point of it. Traces the development of the number of Connecting Digits from two in Ed 1 (1933) to eight in the forthcoming Ed 7 (1967) and the advantages of it. Outlines the main changes in Ed 7 of CC and shows that they mostly consist of changing the Connecting Digit of Time Facet and of changing the Connecting Digit of certain isolates hitherto taken as Energy Isolates and now taken as Property Isolates — that is, manifestations of Matter. Some newly emerging Main Classes have been given Class Numbers. The paper is by way of soliciting suggestions and remarks on the proposed changes from the colleagues in the profession.